Stability Analysis of the Lining Reinforcement Structure of a Double-Track Heavy-Haul Railway Tunnel - Weibin Ma; Jinfei Chai; Xiaoyan Du; Yao Li; Peng Zhao; Shanduo Li (Advances in Civil Engineering)
An increasing number of railway tunnels are afflicted with railway tunnel lining diseases. Through on-site detection of lining diseases in double-track railway tunnels, this paper analyzed its causative factors and developed a section steel arch frame lining reinforcement. Through a simulation of its mechanical performance, both the steel plate and concrete met the tensile strength code requirements for railway tunnel design (TB 10003-2016). It effectively repaired the damage from lining diseases under narrow-site and short maintenance “window” time conditions without affecting the normal operation of catenary and power supply facilities. This reinforcement has great practical significance and broad application prospects.